2021
DOI: 10.1093/ijnp/pyab009
|View full text |Cite
|
Sign up to set email alerts
|

Rewarding Subjective Effects of the NMDAR Antagonist Nitrous Oxide (Laughing Gas) Are Moderated by Impulsivity and Depressive Symptoms in Healthy Volunteers

Abstract: Background Nitrous oxide (N2O) is an anaesthetic gas with both therapeutic and abuse potential. As an NMDAR antagonist, its effects are expected to resemble those of the prototypical NMDAR antagonist, ketamine. Here, we examine the subjective rewarding effects of N2O using measures previously employed in studies of ketamine. We also test for moderation of these effects by bipolar phenotype, depressive symptoms, and impulsivity. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 68 publications
0
15
0
Order By: Relevance
“…Moreover, in humans, high impulsivity has been positively correlated with high opioid receptor concentrations in the brain, particularly in regions important for motivational behavior and substance abuse ( Love et al, 2009 ). Significantly, Kamboj et al (2021) observed a positive correlation between liking for N 2 O and impulsivity. Since subanaesthetic N 2 O and ketamine have opioid properties ( Smith et al, 1987 ; Sarton et al, 2001 ; Matussek, 2003 ; Emmanouil and Quock, 2007 ; for additional references, see Gillman, 2019a , 2019b), these observations ( Kamboj et al, 2021 ) are more likely to have been due to opioid activity rather than NMDAR blockade.…”
mentioning
confidence: 86%
See 4 more Smart Citations
“…Moreover, in humans, high impulsivity has been positively correlated with high opioid receptor concentrations in the brain, particularly in regions important for motivational behavior and substance abuse ( Love et al, 2009 ). Significantly, Kamboj et al (2021) observed a positive correlation between liking for N 2 O and impulsivity. Since subanaesthetic N 2 O and ketamine have opioid properties ( Smith et al, 1987 ; Sarton et al, 2001 ; Matussek, 2003 ; Emmanouil and Quock, 2007 ; for additional references, see Gillman, 2019a , 2019b), these observations ( Kamboj et al, 2021 ) are more likely to have been due to opioid activity rather than NMDAR blockade.…”
mentioning
confidence: 86%
“…Significantly, Kamboj et al (2021) observed a positive correlation between liking for N 2 O and impulsivity. Since subanaesthetic N 2 O and ketamine have opioid properties ( Smith et al, 1987 ; Sarton et al, 2001 ; Matussek, 2003 ; Emmanouil and Quock, 2007 ; for additional references, see Gillman, 2019a , 2019b), these observations ( Kamboj et al, 2021 ) are more likely to have been due to opioid activity rather than NMDAR blockade.…”
mentioning
confidence: 86%
See 3 more Smart Citations